Analyzing Nepali Language Teaching in Multilingual Context: A Systematic Review - Gautam, Basu Dev (Yayasan Sembilan Pemuda Indonesia, 2024)
In this qualitative study, how native languages impact second language acquisition among Nepalese students learning Nepali has been analyzed. Utilizing secondary data, it examines the distinct processes shaped by diverse linguistic backgrounds. First language acquisition occurs naturally through family interaction, while second language learning happens in formal settings, influenced by social and educational needs. The study finds that the ease of acquiring Nepali/English as a second language is inversely related to the structural differences between the learner’s first and second languages. Closely aligned linguistic structures facilitate easier learning, while significant differences present challenges. The study emphasizes the need for adaptive teaching methodologies that accommodate Nepal's multilingual classrooms. This approach aims to improve academic and social integration among learners.Creating supportive and immersive learning environments can enhance the natural acquisition of Nepali, fostering greater linguistic competence and confidence.